1996
DOI: 10.1016/0370-2693(96)00669-7
|View full text |Cite
|
Sign up to set email alerts
|

Dressing cosets

Abstract: The account of the Poisson-Lie T-duality is presented for the case when the action of the duality group on a target is not free. At the same time a generalization of the picture is given when the duality group does not even act on σ-model targets but only on their phase spaces. The outcome is a huge class of dualizable targets generically having no local isometries or Poisson-Lie symmetries whatsoever.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(142 citation statements)
references
References 34 publications
2
140
0
Order By: Relevance
“…In order to answer these questions we work with the first-order action on a Drinfel'd double D [37,38] and its generalisation to coset spaces [42,43]. As a vector space, the Lie algebra of the Drinfel'd double d = Lie(D) can be decomposed as…”
Section: Jhep11(2017)014mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to answer these questions we work with the first-order action on a Drinfel'd double D [37,38] and its generalisation to coset spaces [42,43]. As a vector space, the Lie algebra of the Drinfel'd double d = Lie(D) can be decomposed as…”
Section: Jhep11(2017)014mentioning
confidence: 99%
“…The backgrounds for cases (i) and (ii) were constructed in [36,42] for a matrix E 0 depending on two parameters. In [16] it was shown that in the special case 57) in the ǫ → 0 limit, these backgrounds correspond to those of the η and λ * deformations respectively.…”
Section: Jhep11(2017)014mentioning
confidence: 99%
“…The interest of the O(3) sigma model and its non Abelian dual stems from the fact that the fields of the former parametrize a coset space while usually non Abelian duality is formulated for sigma models defined on group manifolds; see however ref. [25] for Poisson Lie duality in case of cosets.…”
Section: Discussionmentioning
confidence: 99%
“…The problem with this is that the generating functional, (17), is independent of g, yet for g = −1 the ψ field of the O(3) and the α field of the dual models decouple. In the Hamiltonian formalism, these decouplings can be handled in general by the procedure described in [25]. In the present case, the canonical transformation connecting these two models can be described by the following generating functional…”
Section: The Canonical Transformationmentioning
confidence: 99%
See 1 more Smart Citation